The influence of anxiety on speaking english in tenth grade students at unidad educativa José Mejía Lequerica. - Delgado Yagual, Jane Odalis (2023)
Language anxiety poses a significant challenge for students when learning a new language, particularly in the context of speaking. This research delves into the influence of anxiety on English speaking proficiency in tenth grade students at Unidad Educativa José Mejía. The study aims to understand how anxiety influences language competence and confidence and proposes strategies to mitigate its impact. Drawing on a qualitative approach, a focus group of five proficient English-speaking students with anxiety-related challenges was formed. Through open questions, participants' experiences, perceptions, and anxiety management strategies were explored. The research examined existing theories on language anxiety, emphasizing its causes, manifestations, and consequences in language learning. Additionally, the study highlights the significance of addressing language anxiety in educational settings and reviews existing strategies to manage and overcome it. The findings provide deeper insights into students' experiences and the effects of anxiety on English speaking. Identified patterns and effective anxiety management strategies are discussed in conjunction with the existing literature. Recommendations for educators, students, and future research are offered. Ultimately, this research seeks to promote confidence and proficiency in English speaking, fostering improved learning experiences and outcomes by creating inclusive and supportive learning environments that address language anxiety.